2020
DOI: 10.1080/22423982.2020.1749001
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations of cold sensitivity – a case series

Abstract: Objectives: To characterise cold sensitivity using a semi-structured interview, physical examination, thermal quantitative sensory testing (QST), and laser speckle contrast analysis (LASCA). Methods: Eight women and four men, ages 22-74, with cold sensitivity were interviewed and examined by an occupational physician. Thermal perception thresholds were established using QST, on the pulp of the index and little finger of the most affected hand. Skin perfusion in the dorsum of the hand was measured using LASCA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Finally, the questionnaire implies the assumption that an injury has occurred, preceding the onset of cold sensitivity. As has been shown previously, this is not always the case (Campbell and Kay, 1998;Stjernbrandt et al, 2020;Vaksvik et al, 2016). However, one major strength is the size of the present study, compared with previously reported reference materials.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Finally, the questionnaire implies the assumption that an injury has occurred, preceding the onset of cold sensitivity. As has been shown previously, this is not always the case (Campbell and Kay, 1998;Stjernbrandt et al, 2020;Vaksvik et al, 2016). However, one major strength is the size of the present study, compared with previously reported reference materials.…”
Section: Discussionmentioning
confidence: 60%
“…Finally, question six asks for consequences for daily living, but uses activities not typically recognized to be a problem for subjects with cold sensitivity (e.g. 'dressing and undressing' or 'tying shoelaces'), according to an interview study on subjects with cold sensitivity (Stjernbrandt et al, 2020). In addition, no information is gathered on the distribution of cold sensitivity, which means that CISS scoring is unchanged by describing symptoms in only one finger, compared with both whole arms, as long as the perceived consequences are the same.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent research by ( Stjernbrandt et al, 2020 ) aimed to characterize cold sensitivity utilizing a comprehensive approach including semi-structured interviews, physical examination, thermal quantitative sensory testing (QST), and laser speckle contrast analysis (LASCA). Their findings challenge conventional neurosensory pathophysiological hypotheses by demonstrating limited diagnostic aid from physical examination and thermal QST.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has employed various terms such as cold sensitivity ( Stjernbrandt, 2018 , 2020 ), cold hypersensitivity ( Park and Cha, 2017 ), hiesho (sensitivity to cold) ( Nakamura and Horiuchi, 2013 , 2017 ), and hiesho (cold disorder) ( Kimura and Asami, 2016 ; Mori et al, 2018 ; Sakaguchi et al, 2016 , 2016 ; Yoshino et al, 2013 ), leading to confusion in research comparisons. To clarify, perceived cold sensitivity reflects individuals' subjective awareness of feeling sensitive to cold in daily life, providing insight into their experiences.…”
Section: Introductionmentioning
confidence: 99%
“…The latter has been the focus of much research, and for vibration-induced RP the prognosis has been described to be somewhat better as compared to neurosensory injury, where roughly half of symptomatic subjects can improve if exposure to HAV is ceased [ 16 ]. Finally, abnormal cold sensitivity is an ambiguous symptom that can be related both to neural and vascular dysfunction [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%